Virtual reality as a physical therapy resource in cardiorespiratory treatment: A systematic review (Research, Society and Development, 2021)
This systematic review aimed to verify on main literature evidence related to virtual reality (VR) used for cardiorespiratory physical therapy. The search for studies was performed in LILACS, PubMed, PEDro, Scielo and Scopus databases. Original studies that addressed use of VR in cardiorespiratory physical therapy treatment in Portuguese, English and Spanish were selected. During the search, four hundred fifteen studies were found, of which five studies met the inclusion criteria. The studies were submitted to risk of bias judgment using the Cochrane Risk of Bias Tool. From five studies selected, none showed a high risk of bias. Four studies used non-immersive VR as an auxiliary resource. Three studies were conducted in inpatient and two in outpatient settings. Two studies assessed functional capacity using FIM and three studies used 6MWT to assess cardiorespiratory capacity. Only one study evaluated acute hemodynamic effects produced by VR in therapy and another evaluated pulmonary function through the evaluation of maximal inspiratory and expiratory forces. All VR treatments were associated with kinesiotherapy. It was concluded that VR as a coadjuvant method in cardiorespiratory physiotherapy treatment, both in hospital and outpatient settings, presents results similar to conventional treatment in improving functional and physical capacity, with motor and respiratory benefits.